The relationship between peer conformity and hedonic lifestyle in students - Yetti, Nurul Islami; ifdil, ifdil (JPGI (Jurnal Penelitian Guru Indonesia), 2023)
This study aims to analyze and evaluate the relationship between peer conformity and hedonic lifestyle in students. The type of research used is a descriptive and correlational quantitative approach. The sample in this study was SMAN 1 Tigo Nagari, which consisted of 170 students. The data analysis technique used was descriptive analysis and pearson product moment correlation analysis with the help of the JASP version 16.3 program. the results of the study revealed that peer conformity among students was generally in the moderate category, and the hedonic lifestyle of students was in the moderate category, and there was a significant relationship between peer conformity and the hedonic lifestyle of students.